2017
DOI: 10.1016/j.ijsu.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of thromboembolism prophylaxis with fondaparinux in Japanese colorectal cancer patients undergoing laparoscopic surgery: A phase II study

Abstract: There were no cases of PE. It is necessary to establish strict criteria for VTE prophylaxis with FPNX after LAC for Japanese patients considering the incidence of bleeding events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A search of PubMed, PubMed Central, and Google Scholar for the terms “colon or colorectal surgery” and “VTE” and of reference lists of retrieved articles identified 20 relevant papers . Many of these studies were retrospective analyses that relied on database searches.…”
Section: Introductionmentioning
confidence: 99%
“…A search of PubMed, PubMed Central, and Google Scholar for the terms “colon or colorectal surgery” and “VTE” and of reference lists of retrieved articles identified 20 relevant papers . Many of these studies were retrospective analyses that relied on database searches.…”
Section: Introductionmentioning
confidence: 99%
“…As a type of anticoagulant, fondaparinux has been widely used to prevent VTE and is considered to have certain clinical advantages in cancer patients ( 18 ). For example, one research shows that the incidence of VTE is 2.5% in colorectal cancer patients who received fondaparinux, which proves that it is effective in VTE prevention ( 19 ). Another study finds that fondaparinux reduces VTE and major bleeding events compared with warfarin in cancer patients ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the bleeding events caused by VTE are also noteworthy. A previous study found that the incidence of major bleeding in patients with colorectal cancer after surgery who received fondaparinux was 1.7% ( 19 ). In our study, similar findings revealed that the rates of the bleeding event in cancer patients who received fondaparinux were 2.68% in the hospital and 0.90% at M1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores range from 0 to 28, with higher scores indicating a better methodological quality of study. The following cut-points have been suggested to categorize studies by quality: excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19), and poor ( < 14).…”
Section: Quality Assessmentmentioning
confidence: 99%